Perspektif Islam Tentang Strategi Pembelajaran - Risna Aulia; Febi Ananda; Gusmaneli Gusmaneli (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
National education faces challenges related to quality, efficiency and management. Several important problems in the education system include: (1) student moral behavior, (2) distribution of learning, (3) less efficient internal systems, (4) poor organization, (5) education management that is not in line with national development, and (6) lack of professionalism in resources. One effort to overcome this problem is to improve learning strategies, which are very important for the success of the learning process. One of the aspects studied in this journal is the teaching of the Islamic religion from Abuddin Nata's perspective. The results of the literature search show that an Islamic-based learning approach can shape student behavior. One effective strategy is to use an approach that is appropriate to the learning objectives and emphasizes skills and learning processes such as the Islamic education model which integrates skills, problem solving and memory formation.